A pilot study: Nailing Indian elections with the indelible ink mark - Anil Abraham; Gillian Roga; Naveen Thomas (Wolters Kluwer Medknow Publications, 2015)
Context: The indelible ink that's used in our elections was developed by National Physical Laboratories (NPL), Delhi in 1962, and has been used ever since. Though formulated by NPL, it is manufactured by Mysore Paints and Varnish Ltd. owned by the Karnataka Government. Earlier, the ink mark was applied on the cuticle but with effect from February 01, 2006 the ink is applied on the voter's left index fingernail from the distal end proximally until the cuticle using an applicator. This idea of the ink mark applied during elections was used as a simple tool to measure the rate of nail growth in a busy outpatient department of a Tertiary Hospital in South India. Aims: To assess the feasibility of using the ink mark during elections as a method of obtaining data of nail growth across the spectrum of the entire country. Subjects and Methods: In 74 patients presenting to a hospital, the rate of nail growth was measured. The voter's mark on the left index fingernail of patients during the recent elections was used as a marker for measuring the length of the nail. Results: The average rate of nail growth was 0.113 mm/day. The rate of nail growth was found to be more in females, younger individuals, pregnancy, patients on nutritional supplementation, psoriasis. Conclusion: This study which was conducted on 74 patients using the election ink mark successfully confirmed the possibility of using it as an efficient tool in measuring the rate of nail growth. The findings revealed the slightly higher rate of nail growth as compared to a study done by Rani et al. However, the limited sample size in this study was the major limitation.